Análise do uso de técnicas de codificação de rede e comunicação full-duplex em rádio cognitivo underlay - Mafra, Samuel Baraldi (2015)
In this work are presented two schemes of cooperative communication for cognitive radio networks limited by the maximum interference level acceptable at the licensed network. The schemes are evaluated in function of the outage probability, that is the probability of failure in the communication. In the first scheme, the unlicensed network is composed by a source, a dedicated full-duplex relay and a destination. Differently of previous works, the system model considers the direct link between the unlicensed transmitter and destination as useful information. The presented analysis includes the effect of the licensed interference, as well as, the self interference at the relay. Moreover, an optimal power allocation (OPA) scheme is proposed. The OPA strategy can choose between two modes of operation, cooperation between source and relay or source transmission only. The proposed OPA scheme has the best performance, when this is compared with concurrent schemes. In the second scheme, the use of network coding is applied in a cognitive scenario where multiple unlicensed users cooperate to send independent messages to the unlicensed destination, thus, in this scenario there are not dedicated nodes to transmission of partner information as in the first scheme. The dynamic network coding (DNC) and generalized dynamic network coding (GDNC) schemes are evaluated in a cognitive scenario, under a given maximum interference constraint set by the licensed network, as well as, the maximum transmit power limit of the unlicensed sources. The cooperation with network coding can provide significant gains in terms of performance, when compared to non cooperative or selective decode-and-forward (SDF) cooperative techniques. Also, a closed-form equation is obtained for the -outage capacity, which is the maximum information rate achieved by the secondary sources given a target outage probability. In order to maximize the -outage capacity of the cognitive GDNC, the optimum number of parity packets is found through Dinkelbach algorithm. A comparison between the two proposed schemes in this thesis, by analysing the use of full-duplex communication in the scheme with network coding, is proposed as a direction for future works.